Answer:
y = 4
x = -6
Explanation:
1/2 x + 1/4 y= -2 first equation
-2/3 x + 1/2 y = 6 second equation
solution:
from the first equation:
8(1/2 x + 1/4 y) = -2*8
8x*1/2 + 8y*1/4 = -16
8x/2 + 8y/4 = -16
4x + 2y = -16 third equation
from the second equation
6(-2/3 x + 1/2 y) = 6*6
6x*-2/3 + 6y*1/2 = 36
-12x/3 + 6y/2 = 36
-4x + 3y = 36 fourth equation
from the third & fourth equation:
4x + 2y = -16
-4x + 3y = 36
0 + 5y = 20
5y = 20
y = 20/5
y = 4
from the fourth equation:
-4x + 3y = 36
-4x + 3*4 = 36
-4x + 12 = 36
-4x = 36 - 12
-4x = 24
x = 24/-4
x = -6
Check:
from the first equation:
1/2 x + 1/4 y = -2
1/2 *-6 + 1/4 * 4 = -2
-3 + 1 0 -2
from the second equation:
-2/3 x + 1/2 y = 6
-2/3 * -6 + 1/2 * 4 = 6
4 + 2 = 6